Metabolome-Wide Association Study of Cord Blood Metabolites With Blood Pressure in Childhood and Adolescence. Issue 12 (16th September 2022) - Zhang, Mingyu; Brady, Tammy M.; Buckley, Jessie P.; Appel, Lawrence J.; Hong, Xiumei; Wang, Guoying; Liang, Liming; Wang, Xiaobin; Mueller, Noel T.
Abstract : Background: No studies have examined whether the cord blood metabolome—a reflection of in utero metabolism—influences blood pressure (BP) in children. Objectives: To examine prospective associations of cord blood metabolites with systolic BP (SBP), diastolic BP (DBP), and risk of elevated BP in childhood and adolescence. Methods: In the Boston Birth Cohort, we measured metabolites in cord blood plasma, and SBP and DBP at clinic visits between 3 and 18 years. We examined associations of cord metabolites with SBP and DBP percentiles using linear mixed models and with elevated BP using mixed-effects Poisson regression. Results: Our study included 902 mother-child dyads (60% Black, 23% Hispanic, 45% female). Children were followed for a median of 9.2 (interquartile range, 6.7–11.7) years, and the median number of BP observations per child was 7 (interquartile range, 4–11). After false discovery rate correction, 3 metabolites were associated with SBP, 96 with DBP, and 24 with elevated BP; 2 metabolites (1-methylnicotinamide, dimethylguanidino valeric acid) were associated with all 3 outcomes, and 21 metabolites were associated with both DBP and elevated BP. After multivariable adjustment, 48 metabolites remained significantly associated with DBP. Metabolites that showed the strongest associations with SBP, DBP, and elevated BP included nucleotides (eg, xanthosine, hypoxanthine, xanthine) and acylcarnitines (eg, C6 and C7 carnitines), which represent fatty acid oxidation and purine metabolism pathways. Conclusions: In our urban and predominantly racial/ethnic minority cohort, we provide evidence that metabolomic alterations in utero, in particular, acylcarnitine- and purine-metabolism metabolites, may be involved in the early life origins of hypertension.